Объяснение:
(x² + 6x)² - 4(x² + 6x + 1) - 17 = 0
t = (x² + 6x)
t² - 4(t + 1) - 17 = 0
t² - 4t - 4 - 17 = 0
t² - 4t - 21 = 0
t² + 3t - 7t - 4 - 17 = 0 (Теорема Виета)
t² + 3t - 7t - 21 = 0
t(t + 3) - 7(t + 3) = 0
(t + 3)(t - 7) = 0
t₁ = -3; t₂ = 7
x² + 6x + 3= 0 x² + 6x - 7 = 0
D = b² - 4ac D = b² - 4ac
D = 6² - 4 * 1 * 3 D = 6² - 4 * 1 * (-7)
D = 36 - 12 D = 36 + 28
D = 24 D = 64
49а²-4с²
0,64а²-b²
25a²-b²
b⁴+16
Объяснение:
(7a-2c)(2c+7a)=(7a-2c)(7a+2c)=(7a)²-(2c)²=49a²-4c²
(0,8a-b)(b+0,8a)=(0,8a-b)(0,8a+b)=(0,8a)²-b²=0,64a²-b²
(-b+5a)(b+5a)=(5a-b)(5a+b)=(5a)²-b²=25a²-b²
(b-2)(b+2)(b²+4)=(b²-2²)(b²+4)=(b²-4)(b²+4)=(b²)²-4²=b⁴+16